Assessment in online and blended learning environments - Koc, Selma; Liu, Xiongyi; Wachira, Patrick (Charlotte, NC Information Age Publishing, 2015)
"Online and blended learning requires the reconstruction of instructor and learner roles, relations, and practices in many aspects. Assessment becomes an important issue in non-traditional learning environments. Assessment literacy, i.e., understanding assessment and assessment strategies, is critical for both instructors and students in creating online and blended environments that are effective for teaching and learning. Instructors need to identify and implement assessment strategies and methods appropriate to online or blended learning. This includes an understanding of the potential of a variety of technology tools for monitoring student learning and improving their teaching effectiveness. From the students’ perspective, good assessment practices can show them what is important to learn and how they should approach learning; hence, engaging them in goal-oriented and self-regulatory cognitions and behaviors. The book targets instructors, instructional designers, and educational leaders who are interested in understanding and implementing either summative or formative assessment in online and blended learning environments. This book will assist the relevant audience in the theory and practice of assessment in online and blended learning environments. Providing both a research and practice perspective, this book can help instructors make the connection between pedagogy and technology tools to maximize their teaching and student learning. Among the questions addressed in this book are: • What assessment strategies can be used in online or blended learning? • How can instructors design effective assessment strategies? • What methods or technology tools can be used for assessment in online or blended learning? • How does peer-assessment work in online or blended learning environments?"
Section I Online Learning and Assessment -- Chapter 1 The value of embedded formative assessment: an integral process in online learning environments implemented through advances in technology -- Chapter 2 Empowering learners to engage in authentic online assessment -- Chapter 3 Assessing technology-enhances learning: a process-orientedd approach -- Chapter 4 Students as "assessors" and "assesses" in an era of social media -- Chapter 5 Assessment methods in online graduate courses -- Chapter 6 Online course dynamic design informed by student response and formative assessment -- Chapter 7 Using embedded audio feedback for formative assessment purposes in teaching about English language learners -- Chapter 8 Assessment strategy for self-paced online learning -- Section II Blended learning and assessment -- Chapter 9 Student assessment in a blended learning environment: a triad approach -- Chapter 10 Contunuous formative assessment during blended and online instruction using cloud-based collaborative documents -- Chapter 11 Blended learning and assessment through dynamic digital portfolios: the E-Scape approach -- Chapter 12 Strategies for success: using formative assessment to build skills and community in the blended classroom -- Chapter 13 /discussion in online and blended learning: a tool for peer assessment -- Chapter 14 Criterion-referenced language assessment in blended environments -- Chapter 15 Framework for assessment from an institutional perspective.
Includes bibliographical references.
Keywords: Blended learning -- Evaluation; Computer-assisted instruction -- Evaluation; Distance education -- Evaluation; Educational tests and measurements -- Data processing; Assessment; Learning assessment